Genomic and biological control of Sclerotinia sclerotiorum using an extracellular extract from Bacillus velezensis 20507 - Cheng, Yunqing; Lou, Hanxiao; He, Hongli; He, Xinyi; Wang, Zicheng; Gao, Xin; Liu, Jianfeng (Frontiers in Microbiology, 2024)
Sclerotinia sclerotiorum is a known pathogen that harms crops and vegetables. Unfortunately, there is a lack of effective biological control measures for this pathogen. Bacillus velezensis 20507 has a strong antagonistic effect on S. Sclerotiorum; however, the biological basis of its antifungal effect is not fully understood. In this study, the broad-spectrum antagonistic microorganisms of B. velezensis 20507 were investigated, and the active antifungal ingredients in this strain were isolated, purified, identified and thermal stability experiments were carried out to explore its antifungal mechanism.The B. velezensis 20507 genome comprised one circular chromosome with a length of 4,043,341 bp, including 3,879 genes, 185 tandem repeats, 87 tRNAs, and 27 rRNAs. Comparative genomic analysis revealed that our sequenced strain had the closest genetic relationship with Bacillus velezensis (GenBank ID: NC 009725.2); however, there were significant differences in the positions of genes within the two genomes. It is predicted that B. velezensis 20507 encode 12 secondary metabolites, including difficidin, macroactin H, fengmycin, surfactin, bacillibacin, bacillothiazole A-N, butirosin a/b, and bacillaene. Results showed that B. velezensis 20507 produced various antagonistic effects on six plant pathogen strains: Exserohilum turcicum, Pyricutaria oryzae, Fusarium graminearum, Sclerotinia sclerotiorum, Fusarium oxysporum, and Fusarium verticillioides. Acid precipitation followed by 80% methanol leaching is an effective method for isolating the antifungal component ME80 in B. velezensis 20507, which can damage the membranes of S. sclerotiorum hyphae and has good heat resistance. Using high-performance liquid chromatography, X-ray diffraction (XRD), and Mass Spectrometry analysis, it is believed that fengycin C72H110N12O20 is the main active antifungal substance. This study provides new resources for the biological control of S. Sclerotiorum in soybeans and a theoretical basis for further clarification of the mechanism of action of B. velezensis 20507.